Integration Of Ecological Principles in the Pesantren System: An Analysis Of Sustainability and Environmental Conservation Practices In Islamic Educational Institutions - Rohmah, Fitri Nur (LP2M IAI AL-KHAIRAT PAMEKASSAN, 2024)
While pesantren education in Indonesia has great potential in implementing ecological principles, challenges in the integration of environmental values often hinder its effectiveness. This study aims to explore the way ecological principles are integrated in the pesantren education system and their impact on environmental conservation practices and awareness of santri. Using a qualitative approach with a descriptive-analytical method, data were collected through in-depth interviews, participatory observation, and document analysis. The findings show that the integration of ecological principles can be effectively implemented through a holistic approach that combines Islamic values with conservation practices. The results reveal that this integration not only increases environmental awareness among santri but also strengthens their Islamic identity as khalifahs responsible for the ecosystem. This research enriches the theory of ecological integration in Islamic education and provides a model that can be applied in other pesantren. Practical implications include guidance for pesantren managers in designing effective environmental curricula and activities. This research also opens pathways for further studies with quantitative or mixed-methods approaches as well as the exploration of digital technology in pesantren environmental education.